Six sigma execution: How to World's greatest companies live and breathe six sigma (sách photo) - Eckes George (American : McGraw-Hill, 2005)
In six Sigma excution, Ecker draws on his vast professional experience to describe the business acumen and leadership skills needed to effectively incorporate Six Sigma into organization's DNA, executing initiatives throughout the entries company. He delivers a practical blueprint that simulates the training and coaching session used with his own clients, providing you with the dialogue, tools, tactics, and cautionary, advice you can use to spearhead and deploy a Six Sigma effort of any size.
In this book, you will discover the characteristics of top Six Sigma leadership as Eckers chronicles the history of the approach from its inception when Bob Galvin incorporated Six sigma into Motorola's operations to larry Bossidy, who linkes Six Sigma to strategic bussiness objectives at Allied Signal and Honeywell to GE's Jack Welch, who was the first to truly create a Six Sigma culture. Also addressed is the work of Jeff Immelt, James McNerney, others. Eckes cites both positive and nigative examples of companies that have operationnalized Six Sigma.
Keywords: Six sigma execution; Management Philosophy; Project Champion